Polymerase Chain Reaction-Assisted Evaluation of the Efficacy of Seed-Treatment Prevention of Sporisorium reilianum Infection in Sorghum Seedlings - Zhang, Zhi; Fan, Juan; Feng, Mucai; Qiu, Hongbo; Hu, Anlong (Frontiers in Microbiology, 2021)
Head smut, caused by Sporisorium reilianum ([Kuhn] Langdon and Fullerton], is a major disease of sorghum. Seed treatment is considered to be the most effective way to control the disease, however, the pathogen can infect at the seedling stage and the infected plant not display symptoms until the reproductive stage is reached. The evaluation of the efficacy of seed-treatments is time consuming and is dependent upon visible symptoms. Polymerase chain reaction (PCR) methods have the ability to identify pathogens and diagnose their presence at an early stage of infection. In this study, the S. reilianum-specific primer SR3 was used for PCR detection pathogen. We optimized temperature, humidity, and spore quantity test conditions and were able to achieve >88% infection incidence in sorghum seedlings. Sorghum seeds were soaked in various concentrations of tebuconazole and planted for 7 days in soil containing 0.2% teliospores. The efficacy of tebuconazole against S. reilianum a was evaluated by PCR and recorded as disease incidence. Results indicated that the reduction in disease incidence after exposure to 0.15, 0.30, 0.45, 0.60, and 0.75 μg/mL tebuconazole was 6.24, 37.48, 67.74, 81.24, and 93.74%, respectively. Significant differences between the concentrations of tebuconazole were observed. The PCR assay represents a valuable tool for evaluating the efficacy of fungicide seed treatments for the control of S. reilianum in sorghum under laboratory conditions.